Tumors, dendritic cells and the danger signal - W. Kowalczyk, Dariusz (Contemporary Oncology/Współczesna Onkologia, 2002)
Neoplastic disease develops as a multistep and multiorgan process. Somatic mutations causing cells transformation lead to uncontrolled cell proliferation, invasion and metastases. Natural factors which could have cytostatic effect on transformed cells in most cases fail to halt tumor growth. Moreover, instead of antitumor activity they might negatively interact with other tissues leading to local or general immunosupression, anemia, cahexia etc. In 1994 Polly Matzinger presented a new theory called the danger model suggesting that specific immune response develops as a result of danger detection rather than discrimination between self and non-self antigens. Although this model refers mainly to immune tolerance its assumptions are valid for such distant subjects as tumors or apparently unrelated with immunology gene therapy. Contemporary self-non-self discrimination model assume that immune system protects the organism against everything which is foreign, thus immune responses are directed towards external entities which are non-self antigens. According to the danger model the immune system detects and then responds to anything whichever is dangerous and not necessarily foreign. In its beganing tumor growth is not recognized as dangerous and does not activate dendritic cells. The lack of dendritic cells activation along with concomitant immunosupression is responsible for the absence of spontaneous immune response against tumor antigens. Antigen delivery in conjunction with the danger signal might thus activate dendritic cells and induce an immune response with a potential to destroy tumor cells.